Effects of Nongenetic Factors on the Birth Weight of Holstein Friesian and Swedish Red Calves under Organic Conditions - Oğuz Fatih Ergün; Veysel Fatih Özdemir; Bahri Bayram (Turkish Journal of Agriculture: Food Science and Technology, 2025)
In this study, the effects of season, gender, parity and year of birth on the birth weight of Holstein and Swedish Reds calves raised under ecological conditions in the eastern Black Sea region of Türkiye were investigated. For this purpose, 985 birth weight records of calves born on a private organic dairy farm were utilized. The data were analyzed by Univariate Analysis of Variance method available in IBM SPSS Statistics 26.0 software. Study results showed that season had a significant (P < 0.01) effect on the birth weight of Holstein Friesian calves. The highest birth weight was observed in the spring season with 42.29 kg. Average birth weight for male calves was 41.8 kg, while female calves weighed 40.4 kg (P < 0.01). First parity dams had the lowest calf birth weight with an average of 38.7 kg. Calves from Holstein cows in second parity had the highest birth weight with 42.8 kg (P < 0.01). The effects of season on the birth weight were statistically significant in Swedish Red calves. Male and female Swedish Reds did not differ significantly with respect to their birth weights. The parity significantly influenced the birth weight of Swedish Red calves in a way (P < 0.05). Calves born from first-parity dams had an average birth weight of 40.3 kg, while those born to multiparous cows had an average of 41.4 kg. Additionally, the year had a notable effect on birth weight, with statistical significance (P < 0.01) observed in both breeds.